Response of Orchid Root Explants (Dendrobium sp.) to The Concentration and Duration Soaking of Hydrogen Peroxide (H2O2) - Mtd, Siti Latipah; Yulianah, Izmi; Agisimanto, Dita (Plantropica: Journal of Agricultural Science, 2026)
Orchids are plants that have aesthetic value and high selling value. The increase in orchid production means that orchid seed propagation needs to develop. Orchid propagation using Root Apical Meristem (RAM) is more effective than Shoot Apical Meristem (SAM) because it does not harm the mother plant. However, orchid seed propagation often fails due to high explant contamination. Therefore, there is a need for analysis regarding the accuracy of sterilization using hydrogen peroxide (H2O2) to reduce contamination rates. This research aimed to study differences in the level of contamination and viability explants in orchid root explants concerning the concentration and duration of soaking in hydrogen peroxide (H2O2). The research was conducted from February to May 2023 at PT Java Indo Arjuna (JAVINA). The experiment in this research uses a 2-factor Completely Randomized Factorial Design (CRFD) in 3 repetitions. The first factor uses 10 levels of H2O2 treatment, and the second factor is 2 orchid species, namely Dendrobium amosmum alba and Dendrobium welirang. Based on the research results, there were no significant differences in the H2O2 treatment and the interaction between the two factors. However, it was found that there were real differences in species factors. Therefore, there were differences in the responses of the two species to the level of contamination, browning and viability explants. The use of H2O2 cannot be used to sterilize explant tissue because of the high percentage of bacterial contamination. However, the use of H2O2 is effective for surface sterilization because the percentage of fungal contamination is low in Dendrobium anosmum alba and Dendrobium welirang.